The Politics of Land Reform in Kenya 2012. (9th April 2014) - Manji, Ambreena
Abstract: This article provides a critique of the final stages of Kenya's land law reform process, which has resulted in the approval of the 2012 Land Act, Land Registration Act, and National Land Commission Act. It argues that in spite of the constitutional and political importance of the new legislation, the process was marked by haste, lack of engagement by legislators, and little participation by citizens. The new laws can be viewed as a deeply disappointing outcome of a decade's struggle over land policy. The article explores the effects of the constitutional deadlines for new legislation; the contradictory role of civil society in relation to the new laws and the bureaucratic structures they create; and the redistributive intentions and potential of the new land legislation.